2005
DOI: 10.1039/b418859d
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and reaction of atmospheric organic vapours on organic films

Abstract: Films composed in whole or in part of organic compounds represent an important atmospheric interface. Urban surfaces are now known to be coated with a film ("grime") whose chemical composition somewhat resembles that of urban atmospheric aerosols. Such films may act as media in which atmospheric trace gases may be sequestered (leading to their removal from the gas phase); they may also act as reactive media, either as a "solvent" or as a source of reagents. Organic coatings on aqueous surfaces are also importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 38 publications
7
64
0
Order By: Relevance
“…As reaction with OH is the dominant loss process of gas-phase PAHs (Atkinson and Arey, 1994), we therefore investigate the heterogeneous reaction rate of OH with particle-phase PAHs to determine its role in the loss of PAHs in Mexico City. Heterogeneous oxidation by ozone may also be an important sink for PAHs (Donaldson et al, 2005), so the results presented here represent a lower limit of their reactive decay.…”
Section: C Marr Et Al: Sources and Transformations Of Pahs In Mementioning
confidence: 99%
“…As reaction with OH is the dominant loss process of gas-phase PAHs (Atkinson and Arey, 1994), we therefore investigate the heterogeneous reaction rate of OH with particle-phase PAHs to determine its role in the loss of PAHs in Mexico City. Heterogeneous oxidation by ozone may also be an important sink for PAHs (Donaldson et al, 2005), so the results presented here represent a lower limit of their reactive decay.…”
Section: C Marr Et Al: Sources and Transformations Of Pahs In Mementioning
confidence: 99%
“…We hypothesize that reactions between O 3 and organic surfaces (i.e., soil, organic films) could be one non-photochemical surface-level source of alkanoic acids near the site, though unlikely to account for the entire source. Reactions of O 3 on organic surfaces such as organic films (Donaldson et al, 2005), plant surfaces (Cape et al, 2009;Jud et al, 2016), and human skin (Liu et al, 2016(Liu et al, , 2017 have been reported previously. Soil organic matter and organic films are often rich in alkenes (Vancampenhout et al, 2009;Donaldson et al, 2005;Simpson et al, 2006), which undergo ozonolysis reactions in the presence of O 3 (Criegee, 1975;Wolff et al, 1997).…”
Section: Alkanoic Acidsmentioning
confidence: 99%
“…Reactions of O 3 on organic surfaces such as organic films (Donaldson et al, 2005), plant surfaces (Cape et al, 2009;Jud et al, 2016), and human skin (Liu et al, 2016(Liu et al, , 2017 have been reported previously. Soil organic matter and organic films are often rich in alkenes (Vancampenhout et al, 2009;Donaldson et al, 2005;Simpson et al, 2006), which undergo ozonolysis reactions in the presence of O 3 (Criegee, 1975;Wolff et al, 1997). Hydroxyalkyl hydroperoxides formed via the ozonolysis of alkenes can further decompose to alkanoic acids (Moortgat et al, 1997;Anglada et al, 2002;Hasson et al, 2003;.…”
Section: Alkanoic Acidsmentioning
confidence: 99%
“…2004; Mmereki et al, 2004;Donaldson et al, 2005;Kahan et al, 2006;Kwamena et al, 2006Kwamena et al, , 2007. The investigated PAHs comprise benzo[a]pyrene (BaP), anthracene, naphthalene, pyrene, phenanthrene, benzo[a]anthracene (BaA), perylene, and fluoranthene.…”
Section: Pah-o 3 -H 2 O Systemmentioning
confidence: 99%